POST-CERTIFICATION TEACHER PERFORMANCE OUTCOME ASSESSMENT: Loso Judijanto*, Melly Susanti - Judijanto, Loso; Susanti, Melly (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
This study uses a purposeless evaluation paradigm to evaluate the classroom action research performance of post-certification teachers. One of the strategies to improve the quality of education in Indonesia is through the use of qualified and professionally competent teaching staff, which is demonstrated by teachers' performance in classroom action research. Attachment to the beneficial, unfavorable, and neutral effects of the post-certification program was assessed. Forty-five teachers with ten or more years of experience and certification as educators were the subjects of the study. Data were collected for this qualitative study approach through the use of questionnaires, interviews, documentation, and observation. The results showed that although teacher performance in classroom action research has not improved, the certification program in improving teacher welfare has provided benefits.